Intraindividual comparison of image quality using retrospective and prospective respiratory gating for the acquisition of thin sliced four dimensional multidetector CT of the thorax in a porcine model. (21st October 2015) - Behzadi, Cyrus; Groth, Michael; Henes, Frank Oliver; Schwarz, Dorothee; Deibele, André; Begemann, Philipp GC; Adam, Gerhard; Regier, Marc
ABSTRACT: Purpose: To intraindividually compare image quality and anatomical depiction of the lung and mediastinum using retrospective and prospective respiratory gating techniques for the acquisition of 4D-multidetector computed tomography (MDCT) of the chest in a porcine model. Materials and Methods: Twelve trachealy intubated domestic pigs underwent 64-row MDCT of the thorax. For retrospective and prospective gating the automated respiratory frequency was adjusted to 10, 14, 18, and 22 respiratory cycles per minute. Further, free breathing MDCT scans of the lung were performed at the same respiratory settings. A breathhold scan was acquired which served as the reference standard. Three reviewers independently analyzed the MDCT data applying a 4-point-grading scale regarding the degree of artifacts observed and anatomical depiction (1, excellent, no artifacts; 4, nondiagnostic due to severe artifacts). For statistical analysis the Wilcoxon matched pairs and Chi-square test were used. Results: Breathhold imaging allowed for the highest image quality (mean value: trachea, 1.00; bronchi, 1.10; lung parenchyma, 1.08; diaphragm, 1.00; pericardium, 1.80). Retrospective gating proved to be of superior image quality compared to prospective gating for all respiratory frequencies. With the respiratory frequency set to 14/min retrospective gating even enabled an identical image quality score as at breathhold. Performing image acquisition during continuous breathing lead to a severe decrease in image quality. Conclusions: High image quality can be acquired using respiratory gating techniques for 4D-MDCT of the thorax. Retrospective is superior to prospective gating and can be of an equivalent image quality as standard breathhold imaging, but at the cost of a significantly higher radiation dose.